18F-NaF Uptake in Calcified Uterine Leiomyoma. (November 2019) - Kothekar, Esha; Raynor, William Y.; Werner, Thomas J.; Alavi, Abass; Baker, Joshua F.
Abstract : Abstract: Uterine leiomyomas (fibroids) represent the most common benign pelvic tumors in women as well as the leading indication for hysterectomies in the United States. Risk factors for the development of fibroids include increasing age, hormonal changes, genetics, and race, among others. The lifetime risk of developing fibroids is greater than 80% among African American women, who also have the more severe form of this condition. We are presenting a case of incidental 18 F-NaF uptake in the calcified uterine leiomyoma of a 52-year-old African American woman.